SPECIALIZED ADMINISTRATIVE COURTS REPUBLIC OF KAZAKHSTAN - Ablaeva, Эльвира Бекболатовна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
The paper describes the historical path of formation and formation of the administrative courts of the Republic of Kazakhstan as specialized. The directions of development of specialized administrative courts, improvement of the quality of their consideration of administrative cases, as well as improvement of administrative proceedings are outlined. Explanations of the term’s administrative justice, administrative proceedings, administrative process and many others are given. The relevance of the topic is related to the conceptual directions of the development of the judicial system, the improvement of judicial proceedings and the improvement of judicial professionalism in accordance with the principle of specialization of courts and judges. The organizational and functional state of specialized administrative courts of Kazakhstan has been analyzed and evaluated. The study of these issues showed that they are formed according to the type of inter-district courts in cities of republican and regional significance, constitute the lowest level of courts of general jurisdiction, consider administrative cases arising from public legal relations, according to the rules of the court of first instance. Specialized administrative courts are analogous to administrative justice courts operating in a number of foreign countries, modeled after the Anglo-Saxon, French or German models. The theoretical significance of the work is that it analyzes the organizational and procedural foundations of the activities of specialized administrative courts in the context of the principle of specialization of courts and judges, which forms the basis of the structure and functioning of the unified judicial system headed by the Supreme Court of the Republic of Kazakhstan. The practical significance of the work is the conclusions formulated by the author, which can be used for scientific research. The methodological foundations of the study testify to the strict observance by the Republic of Kazakhstan of continuity in law and the state. The empirical basis of the work was data on the activities of specialized administrative courts on administrative cases considered by them for the period of the first six months of 2021-2023.